1966
DOI: 10.1139/v66-304
|View full text |Cite
|
Sign up to set email alerts
|

Pyranose–furanose and Anomeric Equilibria: Influence of Solvent and of Partial Methylation

Abstract: Sugars possessing the arabino (2,3,4-trans,cis) configuration exist a s furanoses to a greater extent in dimethyl sulfoxide than in water. Their 2,3-di-0-methyl derivatives show a n even stronger preference for a five membered ring structure in both solvents. This is most li~arl Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 17 publications
4
36
0
Order By: Relevance
“…In its most general form, such a relation can be written as a power series limited to the second power in cos + A similar angular dependence of the protonproton coupling (J,,,,) for the H-C-0-H fragment has been proposed by a number of authors (2)(3)(4)(5) and in several papers the relation between JHcoH and 4 has been discussed on empirical grounds (6)(7)(8). However, while a functional behavior of the type given by eq.…”
Section: Introductionmentioning
confidence: 89%
“…In its most general form, such a relation can be written as a power series limited to the second power in cos + A similar angular dependence of the protonproton coupling (J,,,,) for the H-C-0-H fragment has been proposed by a number of authors (2)(3)(4)(5) and in several papers the relation between JHcoH and 4 has been discussed on empirical grounds (6)(7)(8). However, while a functional behavior of the type given by eq.…”
Section: Introductionmentioning
confidence: 89%
“…Similar to other six-carbon monosaccharides, it may exist in either linear or cyclic, pyranose or furanose, forms. In aqueous solution, NMR studies have shown that the pyranose form is dominant [210,212,213]. The cyclization leads to the occurrence of two anomeric species, α and β, according to the position of the OH group (see Fig.…”
Section: -Deoxy-d-ribose and Ribosementioning
confidence: 99%
“…60 , À60 or 180 , respectively. Experimental observations in both the solid phase [211,[214][215][216][217]254] and solution [212,213,233] display approximately equal populations of G+ and GÀ conformers, with an almost complete absence of the T conformer. This propensity in glucopyranosides to adopt gauche conformations is known as gauche effect [255, 256 and references therein].…”
Section: -Deoxy-d-ribose and Ribosementioning
confidence: 99%
“…For the monosaccharides, this difference in ranking could be due to a difference in the relative ratios of a to b pyranose anomers, and/or of pyranose to furanose structures, in DMAc or DMAc/LiCl versus the same ratios in water (Franks, 1977). For example, the percentage of glucose a pyranose anomer changes from 38% in water at room temperature to 44% in DMSO at 30°C (Bubb, 2003;Franks, 2000); the amount of furanose anomers of galactose in water at room temperature is 6%, but rises to $15% in DMSO (the temperature of the DMSO experiments does not appear to have been specified by Mackie and Perlin in the original publication) (Mackie & Perlin, 1966); and the amount of furanose anomers of glucose, negligible in both water and DMSO, rises to 4.5% in N,N-dimethyl formamide at 70°C (Reine, Hveding, Kjølberg, & Westbye, 1974). It is also known, from the classic infrared absorption work of Tipson and Isbell, that in water the equilibrium distribution of arabino sugars such as galactose, and of ribo sugars such as talose, is higher in furanose structures than are the equilibrium distributions of xylo (glucose) and lyxo (mannose and gulose) sugars (Tipson & Isbell, 1962).…”
Section: Solution Conformational Entropies In Dmac and Dmac/liclmentioning
confidence: 99%